Unlocking crop resilience: How molecular tools enhance abiotic stress tolerance - Waseem Mushtaq; Jinxin Li; Binbin Liao; Yuhuan Miao; Dahui Liu (Plant Stress)
Abiotic stressors such as salinity, drought, extreme temperatures, and heavy metals threaten crop yield and global food security. Plants respond to these environmental challenges through intricate molecular and physiological processes that regulate stress perception, cellular signalling pathways, and gene expression. Identifying and understanding the roles of key regulatory elements, including transcription factors (TFs) such as NAC, MYB, WRKY, DREB, and microRNAs (miRNAs), has provided new opportunities to boost stress resilience in plants. The combination of advanced sequencing technologies and computational biology has further accelerated the identification of genes responsive to stress and their associated regulatory systems. Among the most promising approaches, the advent of CRISPR/Cas9 gene-editing technology has transformed plant biotechnology by enabling precise, targeted modifications to stress-related genes. Additionally, RNA interference (RNAi) and gene overexpression strategies have been successfully employed to suppress negative regulators and enhance the expression of beneficial genes, respectively. Furthermore, mutant library construction through chemical mutagenesis (e.g., ethyl methanesulfonate (EMS)-induced mutations) and Agrobacterium-mediated transformation has contributed to the identification of novel genes involved in stress responses. Despite these advancements, challenges remain in translating laboratory findings into field applications due to complex gene-environment interactions and regulatory hurdles. However, the integration of genome editing with conventional breeding, omics technologies, and synthetic biology offers promising avenues for developing climate-resilient crops. This review explores recent breakthroughs in plant biotechnology for abiotic stress tolerance, highlighting the potential of CRISPR/Cas9 and other molecular tools in addressing the increasing demand for food production under changing climatic conditions.